Leaf dimensions and photosynthesis of Rhizophora mangle in estuarine areas under contrasting hydrological conditions - Barboza, Flora; Medina, Ernesto (Boletín del Centro de Investigaciones Biológicas, 2024)
In El Tablazo Bay and the mouth of the Maracaibo Strait (≈ 10.7º–11.1º N; 71.6º–71.8º W) R. mangle communities grow under a semi-arid climate with 500–600 mm annual precipitation. There, the mangrove grows on soils with no apparent nutritional limitations (N, P) and moderate salinity (7–9 ‰), reaching average heights of around 17 m. Leaf dimensions and light saturated photosynthesis were measured in two areas subjected to hydrological regimes causing differences in the sediment concentrations of K, Na y N. The leaf mass/area ratios (157–173 g m-2) were within the margins reported for R. mangle over a wide latitudinal and precipitation range, but without nutritional deficiencies. The average succulence (268–282 g water m-2) reached values similar to those of Caribbean mangroves, but lower than the average observed in higher salinity sites. Mean rates of photosynthesis (11.3–12.2 μmol m-2 s-1) and stomatal conductance (149–172 mmol m-2 s-1) coincided with those of non-nutrient-limited communities across the latitudinal range of the species. The edaphic differences in the studied sites are reflected in variations in leaf mass and the degree of succulence, but do not generate significant changes in the gas exchange. The averages of N concentration, conductance, photosynthesis and intrinsic water use efficiency can be used as reference to estimate ecological effects caused by water stress, nutrition, and salinity.